2016
DOI: 10.1073/pnas.1608319113
|View full text |Cite
|
Sign up to set email alerts
|

Loss of TRIM33 causes resistance to BET bromodomain inhibitors through MYC- and TGF-β–dependent mechanisms

Abstract: Bromodomain and extraterminal domain protein inhibitors (BETi) hold great promise as a novel class of cancer therapeutics. Because acquired resistance typically limits durable responses to targeted therapies, it is important to understand mechanisms by which tumor cells adapt to BETi. Here, through pooled shRNA screening of colorectal cancer cells, we identified tripartite motif-containing protein 33 (TRIM33) as a factor promoting sensitivity to BETi. We demonstrate that loss of TRIM33 reprograms cancer cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 49 publications
2
38
0
Order By: Relevance
“…We showed that GS-626510, a novel oral BET inhibitor, has remarkable activity against chemotherapy-resistant cell lines not only in vitro but also in vivo against xenografts and PDXs established from patients harboring chemotherapy-resistant tumors. These preclinical data with JQ1 and GS-626510 in primary ovarian cancer cell lines and xenografts confirm and expand the results of recent in-tumor shRNA genetic screens revealing c-MYC overexpression as a therapeutic target in chemotherapy-resistant tumors through the use of BRD4 inhibitors (27,28). While previous studies have found that some ovarian tumors may contain BRD4 amplifications and that such tumors may respond to BET inhibition (29), the prevalence of these amplifications in ovarian cancer tends to be low (30).…”
Section: Discussionsupporting
confidence: 80%
“…We showed that GS-626510, a novel oral BET inhibitor, has remarkable activity against chemotherapy-resistant cell lines not only in vitro but also in vivo against xenografts and PDXs established from patients harboring chemotherapy-resistant tumors. These preclinical data with JQ1 and GS-626510 in primary ovarian cancer cell lines and xenografts confirm and expand the results of recent in-tumor shRNA genetic screens revealing c-MYC overexpression as a therapeutic target in chemotherapy-resistant tumors through the use of BRD4 inhibitors (27,28). While previous studies have found that some ovarian tumors may contain BRD4 amplifications and that such tumors may respond to BET inhibition (29), the prevalence of these amplifications in ovarian cancer tends to be low (30).…”
Section: Discussionsupporting
confidence: 80%
“…Recently, more potent and specific TBK1 (compound 1) and BET (GS-626510) inhibitors have been described (Jenkins et al, 2018; Shi et al, 2016). We therefore utilized an aggressive KL patient-derived xenograft (PDX) model (DFCI-366) to design a combination therapy schedule for potential future translation to the clinic.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we also used recently described potent and selective TBK1 and BET inhibitors (Jenkins et al, 2018; Shi et al, 2016) as tool compounds to develop a therapeutic strategy with translatable potential for KRAS-driven NSCLC patients. The alternating doublet strategy minimizes the toxicity of inhibiting each target, limits DDI, and also provides a faster path to the clinic compared with triple combination therapies that require complex dose escalation schedules.…”
Section: Discussionmentioning
confidence: 99%
“…2E; refs. 19,43,44), as well as hyperphosphorylation and increased stability due to the inactivation of native E3 ligases such as SPOP or TRIM33 (37,45,46). Many of these mechanisms can be prevented through the use of a BET degrader.…”
Section: Discussionmentioning
confidence: 99%